PENYULUHAN BAHAYA PENGGUNAANA NARKOBA PADA MASYARAKAT DI KAMPUNG TUA TELUK LEGUNG RT.01/RT.02 KECAMATAN NONGSA KOTA BATAM - Nicha Suwalla; Laily Washliati; Lia Fadjriani; Fadlan; Rinawati Siagian (LPPM-Universitas Batam, 2024)
Narcotics are essential for medical treatment and healthcare services. However, if they are misused or used inappropriately according to medical standards, especially if accompanied by illegal drug trafficking, it can result in extremely detrimental effects on individuals or society, particularly the younger generation. Various efforts have been made by the Government to prevent drug abuse in Indonesia. Based on this, the Author is interested in conducting Community Service to provide education in the form of assistance and counseling on the dangers of drug use to the community in Kampung Tua Teluk Legung, Keluruhan Kabil, Nongsa District, Batam City, Riau Islands Province.